2007
DOI: 10.1111/j.1440-1797.2007.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in ocular surface and corneal thickness in relation to metabolic control in patients with chronic renal failure

Abstract: Dry eye and irritational symptoms are major ocular symptoms in CRF patients. Serum calcium and phosphate levels seem to have a prognostic importance for the ocular findings and symptoms in patients with CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 22 publications
4
36
0
7
Order By: Relevance
“…Most of our cases were grade-1 (57%). Aktas et al reported similar results to our study with only grade-1 calcification in 59% of patients (16). However, Dursun et al reported higher proportions, in that 63% of patients were grade-3 to 5 (4).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Most of our cases were grade-1 (57%). Aktas et al reported similar results to our study with only grade-1 calcification in 59% of patients (16). However, Dursun et al reported higher proportions, in that 63% of patients were grade-3 to 5 (4).…”
Section: Discussionsupporting
confidence: 77%
“…This difference among these studies may be associated with the duration of haemodialysis of the patients. The mean duration of haemodialysis was 3.43 years in our study, 3.6 years in Aktas et al's study but 5.0 years in Dursun et al's study (4,16). Hsiao et al also reported a significant relationship between the duration of haemodialysis and the degree of calcification (18).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations